2016
DOI: 10.18632/oncotarget.8165
|View full text |Cite
|
Sign up to set email alerts
|

C-phycocyanin protects against low fertility by inhibiting reactive oxygen species in aging mice

Abstract: Women over 35 have higher rates of infertility, largely due to deterioration of oocyte quality characterized by fragmentation, abnormal meiotic spindle-chromosome complexes, and oxidative stress. C-phycocyanin (PC) is a biliprotein enriched in Spirulina platensis that is known to possess antioxidant, anti-inflammatory, and radical-scavenging properties. D-galactose-induced aging acceleration in mice has been extensively used to study aging mechanisms and for pharmaceutical screening. In this study, adult femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 63 publications
1
31
0
1
Order By: Relevance
“…d ‐gal injections had been reported to cause liver damage and dysfunction, which would lead to an overall morphological change, as well as increase levels or activities of some serum enzymes (Li et al., ). This study showed that ALT and AST levels were significantly elevated in mouse livers injected with d ‐gal for 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…d ‐gal injections had been reported to cause liver damage and dysfunction, which would lead to an overall morphological change, as well as increase levels or activities of some serum enzymes (Li et al., ). This study showed that ALT and AST levels were significantly elevated in mouse livers injected with d ‐gal for 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…13 It has been indicated that C-phycocyanin has expressed anti-inflammatory, antioxidant and radical scavenging properties. 14 In an aspirin-induced gastric ulcer model, spirulina has shown ameliorative effects by alleviating oxidative stress and inflammation. 15 Thus, it is intriguing to ascertain the protective effect of C-phycocyanin in a well-established model of gastric ulcer.…”
mentioning
confidence: 99%
“…Oocytes treated with a single MAM reagent had larger PB1, this was consistent with previous results showing that the single use of dbcAMP, IBMX, or forskolin generated abnormal PB1 due to failed spindle migration (Chen et al, 2012). A high incidence of apoptosis is associated with a reduction in oocyte quality (Li et al, 2016; Wu et al, 2017). We confirmed that the single use of Mil or forskolin caused a higher ratio of apoptosis, suggesting that oocytes incubated with a high concentration of MAM reagents may be of lower quality.…”
Section: Discussionmentioning
confidence: 99%